Can the West Save Africa? - Easterly, William (Journal of Economic Literature, 2009)
In the new millennium, the Western aid effort toward Africa has surged due to writings by well-known economists, a celebrity mass advocacy campaign, and decisions by Western leaders to make Africa a major foreign policy priority. This survey contrasts the predominant “transformational” approach (West comprehensively saves Africa) to occasional swings to a “marginal” approach (West takes one small step at a time to help individual Africans). Evaluation of “one step at a time” initiatives is generally easier than that of transformational ones either through controlled experiments (although these have been oversold) or simple case studies where it is easier to attribute outcomes to actions. We see two themes emerge from the literature survey: (1) escalation—as each successive Western transformational effort has yielded disappointing results (as judged at least by stylized facts, since again the econometrics are shaky), the response has been to try an even more ambitious effort and (2) the cycle of ideas—rather than a progressive testing and discarding of failed ideas, we see a cycle in aid ideas in many areas in Africa, with ideas going out of fashion only to come back again later after some lapse long enough to forget the previous disappointing experience. Both escalation and cyclicality of ideas are symptomatic of the lack of learning that seems to be characteristic of the “transformational” approach. In contrast, the “marginal” approach has had some successes in improving the well-being of individual Africans, such as the dramatic fall in mortality.